The assessment of public ability to purchase residential properties by district in Melaka - Muhammad Adib Ramlee (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2020)
Many people seek to own a house and having a comfortable house is the main objective for most. According to the 10th Malaysia Plan, the focus of housing development in Malaysia is to provide adequate housing to ensure access to homeownership with complete public amenities and good recreational facilities within the neighbourhood for a better living. This corresponds with the National Housing Policy 2018-2025, which ensures the provision of quality housing for all and to improve the accessibility and affordability of homeownership. The Khazanah Research Institute (2015), reported the percentage of homeownership in Malaysia in 2011 was 72.5%, while Melaka constitutes as one of the highest homeownership states in Malaysia with 84.4%. According to the Gross Domestic Product, housing constructions in Malaysia had contributed 4.9 % in 2010 and this increased to 5.0 % in 2017 (DOSM, 2017). Hence, this study will assess the public's ability to purchase residential properties by districts in Melaka. The research objectives of this study are: a) to analyse people's ability to buy residential property, b) to analyse the housing affordability index for three districts in Melaka, c) to analyse the sociodemographic with homeownership ability and d) to propose recommendations for improving the ability of homeownership. A total sample of 400 were selected using stratified random sampling. The study applies various analysis methods such as simple descriptive analysis, relative information index (RII), chi-square, and Pearson correlation analyses. The analysis found that the level of affordability in Melaka by districts improved over the studied year for 2012 (3.4), 2014 (3.0), and 2016 (3.1), from seriously unaffordable to become more affordable. Furthermore, the analysis found that by using RII analysis methods, the criteria in the provision of affordable housing were scored and ranked accordingly as follows: housing price (RII: 0.90), followed by the security (RII:0.89), access to the public facility (RII: 0.88), distance from the working area (RII: 0.88) and location of the house (RII: 0.87). Therefore, several measures were proposed to improve the provision of affordable housing programs such as setting up a comprehensive guideline for the authority and developers which include feasibility and market studies, strategic location, high accessibility to public facilities and amenities as well as good infrastructure provisions.